Outbreak and Eradication of Tropical Rat Mite (Acari: Macronyssidae) in a European Animal Facility. Issue 2 (17th October 2017) - Brito-Casillas, Yeray; Díaz-Sarmiento, Mercedes; García-Arencibia, Moisés; Carranza, Cristina; Castrillo, Antonio; Fernández-Pérez, Leandro; Zumbado-Peña, Manuel; González, Jorge F; Wägner, Ana M
Abstract: A zoonotic, opportunistic out-break of tropical rat mite Ornithonyssus bacoti [Acari: Macronyssidae; Ornithonyssus bacoti (Hirst)] in an animal facility, is described. Immunocompetent mice [ Mus musculus (Linnaeus)] and rat [ Rattus norvegicus (Berkenhout)] strains in a conventional health status facility suffered from scratching and allopecia and staff members suffered from pruritic, erythemato-papular lesions, presumed to be allergic in origin. O. bacoti was identified and treatment with a 0.1% ivermectin solution led to its complete erradication. Safety assessment revealed no signs of acute toxicity in any animal strain. Following this inexpensive strategy, 7 wk after the initial dose, samples were negative for the presence of acari. At the time of this report, 26 months after diagnosis, O. bacoti remains undetected.